Contrasting orthographically similar words facilitates adult second language vocabulary learning. (August 2022) - Baxter, Peta; Bekkering, Harold; Dijkstra, Ton; Droop, Mienke; van den Hurk, Marianne; Leoné, Frank
Abstract: When learners acquire new words in a second language (L2), their lexical representations and links are initially imprecise. As new, similar words are learned, these representations must become more specific to avoid errors. This study investigated whether contrasting similar words triggers this sharpening process and facilitates learning. In a multiple-choice learning task, 114 adults acquired orthographically and semantically similar L2 (pseudo)words by either contrasting them or not. In Experiment 1, participants contrasted the L2 words, and in Experiment 2 they contrasted words in their first language. Only contrasting orthographically similar L2 words facilitated their acquisition. We conclude that contrasting underspecified representations serves as a learning mechanism that guides attention to relevant lexical information. As such, it enables learners to build more specific representations and is conducive to learning. Possibilities for further research and potential implications for L2 vocabulary instruction are discussed. Highlights: 114 adults learned orthographically and semantically similar words in a multiple-choice learning task. Half of the learners contrasted similar words, the other half did not. Contrasting occurred in the second language (Experiment 1) or the first language (Experiment 2). Participants who contrasted orthographically similar second language words recalled more of those words on posttests. Contrasting enables learners to build more precise lexical representations, which is conducive to learning.